Dietary Polyphenols Consumption and Its Relation with Cognitive and Mental Health in Aging: A Review - Hanisah Rosli,; Suzana Shahar,; Normah Che Din,; Hasnah Harun, (Penerbit UKM, 2014)
Literature review suggests that polyphenols in particular fl avonoids, are benefi cial for mental health during aging process. This review examines the effect of consumption of all polyphenols groups on mental health and cognitive status during aging process. The keywords searched were “mental health,” “depression,” “anxiety,” “stress” and “cognitive” combined with “dietary,” and “polyphenols.” The databases including PubMed, Web of Science and CAB Abstracts were searched for a period of 10 years. A total of 11 studies were identifi ed to fulfi ll the inclusion criteria. From this review, polyphenols may confer benefi cial effects towards mental health, in particular the decline in cognitive functions during aging process, however, some studies showed contradictory results. Polyphenols have been proven to improve language and verbal ability, which is among the main vulnerable aspects in cognitive decline in pathological brain aging. In contrast, polyphenols intake did not seem to affect executive functioning. The effects of polyphenols towards cognitive status were more prominent among the elderly as compared to young and middle-aged adults. This review also shows that fl avonoids is the main type of polyphenols that confer positive effects towards cognitive status during aging. This review provides evidence that consumption of polyphenols may lead to cognitive and mental health benefi ts. Further clinical trials involving human subjects are required with carefully designed methodology to elucidate the potential mechanisms underlying the relationship between polyphenols consumption and improvement in cognitive and mental health status